The Effect of Topoisomerase I Inhibitors on the Efficacy of T-Cell-Based Cancer Immunotherapy. (18th December 2017) - McKenzie, Jodi A; Mbofung, Rina M; Malu, Shruti; Zhang, Min; Ashkin, Emily; Devi, Seram; Williams, Leila; Tieu, Trang; Peng, Weiyi; Pradeep, Sunila; Xu, Chunyu; Zorro Manrique, Soraya; et al.
Abstract: Background: Immunotherapy has increasingly become a staple in cancer treatment. However, substantial limitations in the durability of response highlight the need for more rational therapeutic combinations. The aim of this study is to investigate how to make tumor cells more sensitive to T-cell-based cancer immunotherapy. Methods: Two pairs of melanoma patient-derived tumor cell lines and their autologous tumor-infiltrating lymphocytes were utilized in a high-throughput screen of 850 compounds to identify bioactive agents that could be used in combinatorial strategies to improve T-cell-mediated killing of tumor cells. RNAi, overexpression, and gene expression analyses were utilized to identify the mechanism underlying the effect of Topoisomerase I (Top1) inhibitors on T-cell-mediated killing. Using a syngeneic mouse model (n = 5 per group), the antitumor efficacy of the combination of a clinically relevant Top1 inhibitor, liposomal irinotecan (MM-398), with immune checkpoint inhibitors was also assessed. All statistical tests were two-sided. Results: We found that Top1 inhibitors increased the sensitivity of patient-derived melanoma cell lines (n = 7) to T-cell-mediated cytotoxicity ( P < .001, Dunnett's test). This enhancement is mediated by TP53INP1, whose overexpression increased the susceptibility of melanoma cell lines to T-cell cytotoxicity (2549 cell line: P = .009, unpaired t test), whereas its knockdown impeded T-cell killing of Top1 inhibitor–treated melanoma cells (2549 cell line: P < .001, unpaired t test). In vivo, greater tumor control was achieved with MM-398 in combination with α-PD-L1 or α-PD1 ( P < .001, Tukey's test). Prolonged survival was also observed in tumor-bearing mice treated with MM-398 in combination with α-PD-L1 ( P = .002, log-rank test) or α-PD1 ( P = .008, log-rank test). Conclusions: We demonstrated that Top1 inhibitors can improve the antitumor efficacy of cancer immunotherapy, thus providing the basis for developing novel strategies using Top1 inhibitors to augment the efficacy of immunotherapy.